We need to find the value of lim x--> pi/4 [sin x/(1- 2*(sin x)^2) - cos x/2*(cos x)^2 - 1) - sin 2x / cos x.

Substituting x = pi/4, gives us an indeterminate value.

lim x--> pi/4 [sin x/(1- 2*(sin x)^2) - cos x/(2*(cos x)^2 - 1) - sin 2x / cos x

use (1- 2*(sin x)^2) = 2*(cos x)^2 - 1 = cos 2x

=> lim x--> pi/4 [ sin x/cos 2x - cos x/cos 2x - sin 2x/cos x]

=> lim x--> pi/4 [ (sin x - cos x)/cos 2x - sin 2x/cos x]

=> lim x--> pi/4 [ (sin x - cos x)/( (cos x)^2 - (sin x)^2) - sin 2x/cos x]

=> lim x--> pi/4 [ -1/(cos x + sin x) - sin 2x/cos x]

sin pi/4 = cos pi/4 = 1/sqrt 2

substituting x = pi/4

=> -1/((1/sqrt 2) + (1/sqrt 2)) - 1/(1/sqrt 2)

=> -1/sqrt 2 - sqrt 2

=> -3/sqrt 2

**The required limit is -3/sqrt 2**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now